Presynaptic calcium currents and their relation to synaptic transmission: Voltage clamp study in squid giant synapse and theoretical model for the calcium gate - Llinás, Rodolfo (1976)
A voltage clamp study of the presynaptic terminal in squid stellate ganglion has given quantitative results relating inward Ca(2+) current to presynaptic membrane potential and postsynaptic response to inward Ca(2+) current. The results indicate an S-shaped curve for the relationship between presynaptic potential and Ca(2+) current and a linear relationship between Ca(2+) current and postsynaptic potential. A similar S-shaped curve was found for the time-dependent properties of the Ca(2+) conductance. Based on these results a mathematical model was developed which accounts for the experimental results in this and previously published papers by other authors. The model suggests that five subunits are involved in the Ca(2+) gate and that the subunits change noncooperatively from an inactive to an active form upon membrane depolarization.